2021
DOI: 10.3390/toxics9110271
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Patterns of DNA Methylation in Procambarus clarkii Following Exposure to Genotoxicants: A Conjugation in Past Simple or Past Continuous?

Abstract: Epigenome is susceptible to modulation by environmental pressures—namely, through alterations in global DNA methylation, impacting the organism condition and, ultimately, reverberating on the phenotype of the subsequent generations. Hence, an intergenerational study was conducted, aiming to clarify the influence of genotoxicants on global DNA methylation of the crayfish Procambarus clarkii. Two subsequent generations were exposed to the herbicide penoxsulam (Px; 23 µg·L−1) and to the genotoxicant model ethyl m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Several other papers have been published dealing with the effects of pesticides on the methylation status of whole-animal genomes or specific genes. Marçal et al [ 21 ] found that the herbicide penoxsulam did not induce global DNA methylation changes in the F 0 generation of crayfish Procambarus clarkii but did find hypomethylation in unexposed F1 crayfish, indicating that events occurring in previous generations might have an impact on subsequent ones. Terrazas-Salgado et al [ 22 ] reviewed studies using zebrafish as an animal model to study the effect of xenobiotics, such as pesticides, drugs, or endocrine disruptors, on transgenerational epigenetic processes, particularly global or gene-specific DNA methylation, e.g., the methylation of FOXA2 (forkhead box protein A2) or rRNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…Several other papers have been published dealing with the effects of pesticides on the methylation status of whole-animal genomes or specific genes. Marçal et al [ 21 ] found that the herbicide penoxsulam did not induce global DNA methylation changes in the F 0 generation of crayfish Procambarus clarkii but did find hypomethylation in unexposed F1 crayfish, indicating that events occurring in previous generations might have an impact on subsequent ones. Terrazas-Salgado et al [ 22 ] reviewed studies using zebrafish as an animal model to study the effect of xenobiotics, such as pesticides, drugs, or endocrine disruptors, on transgenerational epigenetic processes, particularly global or gene-specific DNA methylation, e.g., the methylation of FOXA2 (forkhead box protein A2) or rRNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…By building upon these intriguing findings, subsequent studies validated that exposure to other environmental stimuli, such as bioactive food components, could induce similar epigenomic modulation in artemia, resulting in the generation of robust phenotypes with resistance against V. campbellii over three successive generations [ 98 ]. Furthermore, alterations in water quality parameters, such as ammonia/nitrate levels, and exposure to environmental pollutants can instigate oxidative stress and potentially inflict damage to DNA in crustaceans, thereby potentially modulating epigenetic changes [ 188 , 189 , 190 ]. Additionally, air availability has been shown to influence DNA methylation patterns in kuruma shrimps, coinciding with changes in apoptosis and physiological responses [ 191 ].…”
Section: Applications Of Epigenetics For Immunity Enhancement and Dis...mentioning
confidence: 99%
“…ELS is a high-risk for the development of IBS. Literatures have reported an important epigenetic modulation in sustaining extrinsic phenotypes (Mitrousis et al, 2015;Louwies and Greenwood-Van Meerveld, 2020;Marcal et al, 2021). For example, histone acetylation modification can regulate gene expression and result in long-term abnormal behaviors (Graff and Tsai, 2013).…”
Section: Introductionmentioning
confidence: 99%